The Causal Impact of Migration on US Trade: Evidence from a Natural Experiment - Walter Steingress (Institute for the Study of Labor (IZA), 2015)
Immigrants can increase international trade by shifting preferences towards the goods of their country of origin and by reducing bilateral transaction costs. Using geographical variations across US states for the period 1970 to 2005, we quantify the impact of immigrants on intermediate goods imports. We address endogeneity and reverse causality which arises if migration from a country of origin to a US state is driven by trade opportunities between the two locations by exploiting the exogenous allocation of refugees within the US refugee resettlement program. Our results are robust to an alternative identification strategy, based on the large influx of Central American immigrants to the United States after hurricane Mitch. We find that a 10 percent increase in recent immigrants to a given US state raises intermediate imports from those immigrants' country of origin by 1.5 percent.
Keywords: F14; F22; J61; 330; international trade; international migration; political refugees; hurricane Mitch